2013
DOI: 10.1080/14427591.2013.790668
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Response to Infant Crying: Contributing Factors of the Reciprocal Interaction

Abstract: Infant crying is viewed as a normal and developmental behavior expressed by infants. However, this normal behavior can also be one of the most difficult and trying times for parents. Inconsolable crying is a precipitating factor of shaken baby syndrome. This study explored parents' thoughts, feelings, behaviors, and actions in response to inconsolable infant crying. Using a qualitative research approach, data were collected through participant observations, a questionnaire, and field notes. The results of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…(Wiley et al, 2020)
I had a great support system with friends and family, so people helped and cooked meals. (Cox & Roos, 2008)
Papers that mentioned parents who did not have social support indicated that these parents struggled (Ellett et al, 2005, 2009; Kurth et al, 2014; Poskey et al, 2014).
I basically had no help; I was on the verge of quitting everything.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(Wiley et al, 2020)
I had a great support system with friends and family, so people helped and cooked meals. (Cox & Roos, 2008)
Papers that mentioned parents who did not have social support indicated that these parents struggled (Ellett et al, 2005, 2009; Kurth et al, 2014; Poskey et al, 2014).
I basically had no help; I was on the verge of quitting everything.
…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of included studies reported accounts of parents experiencing significant emotional impact from infant crying (Cox & Roos, 2008 ; Ellett et al, 2009 , 2005 ; Ellett & Swenson, 2005 ; Keefe & Froese‐Fuetz, 1991 ; Kurth et al, 2014 , 2010 ; Landgren & Hallstrom, 2011 ; Landgren et al, 2012 ; Levitzky & Cooper, 2000 ; Long & Johnson, 2001 ; Megel et al, 2011 ; Murray et al, 2018 ; Nash et al, 2008 ; Oaten & Miller, 2019 ; Poskey & Hersch, 2012 ; Poskey et al, 2014 ; Thompson et al, 1986 ; Wade et al, 2005 ; Wiley et al, 2020 ). The two included studies where this subtheme did not emerge focussed specifically on soothing techniques (Drummond et al, 1993 ) and dietary restrictions resulting from infant colic (Kidd et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, providing emotional support and stability meets multiple needs. It corresponds with the child's need to be happy , and also to be safe , as the child gains a sense of emotional security (Morozini, 2015; Poskey et al, 2014; Poskey & Hersch, 2012). These contribute to the child's need to be healthy , with short‐term effects such as settling down to sleep (Evans & Rodger, 2008; Olson, 2004), as well as long‐term implications on the child's psychological wellbeing (Weiber et al, 2018).…”
Section: Resultsmentioning
confidence: 99%